(untitled) (مجلة أبحاث قانونية, 2023)
There is no doubt that the work of a doctor is a humanitarian work aboveall else, based on compassion, honesty, and sound purpose. However, someweak souls may deviate from this principle, those with hard hearts and blindminds,whomaketheirconcernandgoalthecollectionofmoneyfrombehind. Thisprofession,andthepreeminenceinsociety,withouttakingintoaccounttheduties thattheymustadheretoit. Soitisofgreatimportancetoalwaysandneverbealerttowhiletheethicalduties that the doctor must adhere to it while performing this honorableprofession, and this is what I wanted to alert through this paper thatI titled it(The Ethical Responsibility of the Physician in Islamic Low), and I divided thediscussionintotwosections:thefirstdiscussedtheconceptofmoral responsibility and the foundations upon which it is based, and the secondsectiondealtwiththeethicalcontrolsforthosewhopracticemedicalwork Fromthis,Iconcludedmanyconclusions,themostimportantofwhichis thatitisoneofthedutiesTheethicaldoctoristogivethepatienthisfullandundiminished rights, to treat him with kindness, to advise him and be honestindealingwithhim,andtotakeintoaccounthishealth,psychologicaland financialconditions,andthathisobtainingcompensationforhismedicalworkislegislatedbylow,butthatshouldnotbethegoalofthedoctorpracticing this profession, rather it is It is primarily a humanitarian profession, the goalofwhichistohelppeoplepreventillnessfromthembyThe Godwilling. Thisstudyrecommendedtheneedtopayattentiontoraisingyoungchildrenfromayoungagewithsoundmoraleducation,theneedtointroducethe Islamicethicscourseandtheworkethicscourseinthevariousstagesof education,andtheneedformedicalauthoritiestostrivetoestablishethical chartersforworkersinthehealthsector,andtakethenecessarymeasuresandappropriate decisions to activate commitment to them in various areas ofwork.